PHOSPHORUS AVAILABILITY IN OXIDIC SOILS TREATED WITH LIME AND SILICATE APPLICATIONS - Sandim, Aline da Silva [UNESP]; Buell, Leonardo Theodoro [UNESP]; Furim, Ariane Reis [UNESP]; Lima, Gessica da Silva [UNESP]; Nantes Garcia, Jader Luis [UNESP] (Soc Brasileira De Ciencia Do Solo, 2014)
Based on the assumption that silicate application can raise soil P availability for crops, the aim of this research was to compare the effect of silicate application on soil P desorption with that of liming, in evaluations based on two extractors and plant growth. The experiment was carried out in randomized blocks with four replications, in a 3 x 3 x 5 factorial design, in which three soil types, three P rates, and four soil acidity correctives were evaluated in 180 experimental plots. Trials were performed in a greenhouse using corn plants in 20-dm(3) pots. Three P rates (0, 50 and 150 mg dm(-3)) were applied in the form of powder triple superphosphate and the soil was incubated for 90 days. After this period, soil samples were collected for routine chemical analysis and P content determination by the extraction methods resin, Mehlich-1 and remaining P. Based on the results, acidity correctives were applied at rates calculated for base saturation increased to 70%, with subsequent incubation for 60 more days, when P content was determined again. The acidity correctives consisted of: dolomitic lime, steelmaking slag, ladle furnace slag, and wollastonite. Therefore, our results showed that slags raised the soil P content more than lime, suggesting a positive correlation between P and Si in soil. Silicon did not affect the extractor choice since both Mehlich-1 and resin had the same behavior regarding extracted P when silicon was applied to the soil. For all evaluated plant parameters, there was significant interaction between P rates and correctives; highest values were obtained with silicate.
Keywords: phosphorus adsorption; silicate application; liming; silicon-phosphorus interaction